2001
DOI: 10.1021/es0105459
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fe Plaque and Associated Metals on the Roots of Mine-Waste Impacted Aquatic Plants

Abstract: Iron plaque on aquatic plant roots are ubiquitous and sequester metals in wetland soils; however, the mechanisms of metal sequestration are unresolved. Thus, characterizing the Fe plaque and associated metals will aid in understanding and predicting metal cycling in wetland ecosystems. Accordingly, microscopic and spectroscopic techniques were utilized to identify the spatial distributions, associations, and chemical environments of Fe, Mn, Pb, and Zn on the roots of a common, indigenous wetland plant (Phalari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
204
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(230 citation statements)
references
References 53 publications
14
204
0
1
Order By: Relevance
“…Thus, As uptake by rice plants is recognized as a major route of As transfer into food chain which has the potential to become a new disaster for population in Southeast Asia (Heikens et al 2007). Therefore, it is crucial to understand the mechanism of As uptake by rice and to find strategies for reducing As accumulation in grain for enhanced food safety.Paddy rice (Oryza sativa L.) oxygenates its rhizosphere, resulting in the formation of an iron oxyhydroxide plaque (Hansel et al 2001 …”
mentioning
confidence: 99%
“…Thus, As uptake by rice plants is recognized as a major route of As transfer into food chain which has the potential to become a new disaster for population in Southeast Asia (Heikens et al 2007). Therefore, it is crucial to understand the mechanism of As uptake by rice and to find strategies for reducing As accumulation in grain for enhanced food safety.Paddy rice (Oryza sativa L.) oxygenates its rhizosphere, resulting in the formation of an iron oxyhydroxide plaque (Hansel et al 2001 …”
mentioning
confidence: 99%
“…This behavior is itself an efficient mechanism of tolerance in environments contaminated by heavy metals. The formation of iron plaque on roots that can diminish the loss of oxygen is common in aquatic and wetland plants (Møller and SandJensen, 2008) and may influence the availability and mobility of metals in the rhizosphere of aquatic plants (Hansel et. al, 2001).…”
Section: Internal Concentration Of Chromiummentioning
confidence: 99%
“…The formation of iron plaque on the root surfaces of rice and other wetland plants is due to the release of oxygen and oxidants in the rhizosphere and the subsequent oxidation of ferrous to ferric iron and the precipitation of iron oxide or hydroxide on the root surface (Armstrong 1967;Chen et al 1980b;Taylor et al 1984). Mineralogical investigations in wetland fields have shown that the composition of iron plaque in Phalaris arundinacea is mainly ferrihydrite (∼63%) with smaller amounts of goethite (32%) and minor amounts of siderite (5%; Hansel et al 2001), or predominately goethite in Juncus bulbosus (Chabbi 1999) and rice (Chen et al 1980a). Iron plaque therefore has chemical properties similar to those of iron oxides in the soil and can thus sequester both cations and anions and alter the uptake and accumulation of elements by plants.…”
Section: Introductionmentioning
confidence: 99%